Invigorating supply chain performance in small medium enterprises: exploring knowledge sharing as moderator - Arsawan, Wayan Edi; Koval, Viktor; Suhartanto, Dwi; Babachenko, Larysa; Kapranova, Larysa; Suryantini, Ni Putu Santi (Business, Management and Economics Engineering, 2023)
Purpose – This research aimed to evaluate information sharing as a moderating component and examine supply chain performance, including collaboration, capabilities, and innovation. Particularly in the SME sector, since the significance of collaboration and opportunity in supply chains as an SCM trigger is still underdeveloped. Research methodology – To test the hypotheses, data were collected from 179 SMEs in Indonesia, involving 537 managers and assistant managers, and analyzed using partial least square modeling. Findings – The result of cooperation with supply chain partners has led to the gradual improvement of capabilities and innovations, such as improved processes, more efficient operations, better quality, and lower costs. It has also resulted in radical innovation, including introducing new technologies and a change in strategy; thus, it could develop and improve the ability to innovate. Finally, the results helped managers with strategic planning and prioritizing supply chain collaboration to improve capabilities, innovation, and performance. Research limitations – generalizability is limited because of sampling constraints. Practical implications – the results helped managers design strategic planning and prioritize supply chain collaboration to improve capabilities, innovation, and performance. Originality/Value – to the extent of our knowledge, this study is the pioneer investigation into the supply chain in SMEs value-chains in an emerging country from a holistic perspective.